2011
DOI: 10.1111/j.1474-9726.2011.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of superoxide–nitric oxide interactions in the accelerated age‐related loss of muscle mass in mice lacking Cu,Zn superoxide dismutase

Abstract: SummaryMice lacking Cu,Zn superoxide dismutase (SOD1) show accelerated, age-related loss of muscle mass. Lack of SOD1 may lead to increased superoxide, reduced nitric oxide (NO), and increased peroxynitrite, each of which could initiate muscle fiber loss. Single muscle fibers from flexor digitorum brevis of wild-type (WT) and Sod1−/− mice were loaded with NO-sensitive (4-amino-5-methylamino-2′,7′-difluorofluorescein diacetate, DAF-FM) and superoxide-sensitive (dihydroethidium, DHE) probes. Gastrocnemius muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
102
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 64 publications
(109 citation statements)
references
References 51 publications
6
102
0
Order By: Relevance
“…Studies using a combination of immunoblotting, high‐performance liquid chromatography and real‐time fluorescence microscopy methods have monitored specific intracellular RONS in single myofibres isolated from skeletal muscle of SOD1 −/− rodents. These studies carried out in resting and contracting skeletal muscle have demonstrated that genetic ablation of SOD1 does not induce the anticipated increase in cytosolic superoxide availability, but instead induced a substantial increase in peroxynitrite formation 30. These findings may provide important information of the RONS that are implicated in the processes of skeletal muscle ageing and highlight peroxynitrite formation as the important RONS mediator of the exacerbated neuromuscular ageing phenotype observed in the SOD1 −/− model.…”
Section: Non‐enzymatic Key Antioxidants That Contribute To the Maintementioning
confidence: 95%
See 4 more Smart Citations
“…Studies using a combination of immunoblotting, high‐performance liquid chromatography and real‐time fluorescence microscopy methods have monitored specific intracellular RONS in single myofibres isolated from skeletal muscle of SOD1 −/− rodents. These studies carried out in resting and contracting skeletal muscle have demonstrated that genetic ablation of SOD1 does not induce the anticipated increase in cytosolic superoxide availability, but instead induced a substantial increase in peroxynitrite formation 30. These findings may provide important information of the RONS that are implicated in the processes of skeletal muscle ageing and highlight peroxynitrite formation as the important RONS mediator of the exacerbated neuromuscular ageing phenotype observed in the SOD1 −/− model.…”
Section: Non‐enzymatic Key Antioxidants That Contribute To the Maintementioning
confidence: 95%
“…Transgenic mice overexpressing nNOS isoform (nNOS Tg ) also exhibit increased peroxynitrite formation in skeletal muscle 30. However, this model is not associated with changes in skeletal muscle morphology and function, in contrast to the SOD1 −/− murine model 30.…”
Section: Non‐enzymatic Key Antioxidants That Contribute To the Maintementioning
confidence: 99%
See 3 more Smart Citations